2017
DOI: 10.1097/md.0000000000007798
|View full text |Cite
|
Sign up to set email alerts
|

Skin metastases in epithelial ovarian and fallopian tube carcinoma

Abstract: This study aimed to investigate the clinical features and outcomes of skin metastasis in ovarian and fallopian tube carcinomas.We studied patients with epithelial ovarian or fallopian tube carcinoma who developed skin metastasis from 2001 through 2012, and were also treated with chemotherapy and/or surgery.Skin metastases were classified as umbilical metastasis (Sister Joseph nodule [SJN]) and nonumbilical metastasis. Patients who developed skin metastases at paracentesis sites were excluded.Of the 206 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 29 publications
1
31
0
4
Order By: Relevance
“…One additional case, by Banys‐Paluchowski et al, reported a single abdominal subcutaneous implant of a mucinous borderline tumor 9 days after undergoing a laparoscopic unilateral salpingo‐oophorectomy for an ovarian cyst. Consistent with the conclusions of Otsuka et al, this patient's subcutaneous metastasis was likely due to intraoperative seeding of her incision at the time of resection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…One additional case, by Banys‐Paluchowski et al, reported a single abdominal subcutaneous implant of a mucinous borderline tumor 9 days after undergoing a laparoscopic unilateral salpingo‐oophorectomy for an ovarian cyst. Consistent with the conclusions of Otsuka et al, this patient's subcutaneous metastasis was likely due to intraoperative seeding of her incision at the time of resection.…”
Section: Discussionsupporting
confidence: 87%
“…Subcutaneous soft tissue metastasis is a rare feature in gynecologic malignancies, occurring in only approximately 1%‐6% of all epithelial ovarian cancers (EOCs) . Subcutaneous metastases are subdivided by the site of disease into umbilical, also known as Sister Mary Joseph Nodules (SMJN), and nonumbilical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SJNs usually develop in patients with gastrointestinal and gynecological cancers [4,5,6,7,8,9,10]. SJN refers to a metastatic cancer of the umbilicus and is named after Sister Joseph, a nurse who frequently assisted Dr. William Mayo at St. Mary’s Hospital in Rochester, Minnesota, USA.…”
Section: Patterns Of Skin Metastasesmentioning
confidence: 99%
“…Skin metastases usually develop at the umbilicus, surgical scars, including laparoscopic port sites, and in the vicinity of metastatic lymph nodes [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. Skin metastases are often a late manifestation of the disease; however, in certain cases they may sometimes be the first sign of internal malignancies such as lung, renal, and ovarian cancers [47].…”
Section: Introductionmentioning
confidence: 99%